Femoral osteopathy in Gigantspinosaurus sichuanensis (Dinosauria: Stegosauria) from the Late Jurassic of Sichuan Basin, Southwestern China. (13th September 2020) - Hao, Bao-Qiao; Ye, Yong; Maidment, Susannah C; Bertazzo, Sergio; Peng, Guang-Zhao; You, Hai-Lu
ABSTRACT: We report a case of a specific osteopathy in the stegosaurian dinosaur Gigantspinosaurus sichuanensis from the Late Jurassic of Zigong City, China. The G. sichuanensis skeleton is very complete. The left femur has obvious pathological characteristics based on morphological observations. CT scans and energy spectrum data indicate the presence of multiple cystic-like low density areas internal to the pathological area, which are present in the form of multiple cystic low-density shadows in the CT data. This contrasts with the 'normal' area, which does not possess these characteristics. After comparing the specimen with the pathologic scapula of Yangchuanosaurus hepingensis (Dinosauria: Theropoda) also found in Zigong, we consider that the pathology in the left femur of G. sichuanensis was probably caused by a bone tumor. This is the first analysis with the aid of energy spectrum CT scanning of bone disease in fossils. This study increases the known information about paleopathology of stegosaurian dinosaurs and enriches the pathological knowledge of dinosaurs in general.